OBE: OBAT BATUK ENAK OR OUTCOME-BASED EDUCATION? - Ariatna Ariatna (Universitas Negeri Medan, 2022)
Abstract As a result of English globalization and commercialization, the past three decades have seen rapid changes in the field of English Language Teaching (ELT) around the globe. While some English as a Foreign Language (EFL) and English as a Second Language (ESL) nations are satisfied with the adoption of a traditional teacher-centered approach in their English language curriculum, others have opted for a more innovative student-centered approach in an attempt to produce communicatively competent graduates in their countries. Of all the existing student-centered approaches, one approach that has received increasing attention in many EFL/ESL countries is outcome-based education (hereinafter referred to as OBE). As an innovative model of pedagogy, this approach focuses on student learning outcomes which can be measured through what students know and what they can actually do upon completion of a course. This article provides an overview of the basic concepts of OBE and how it has developed across instructional contexts. To provide an objective perspective, the merits and downsides of OBE are also discussed along with some implementational possibilities and challenges. At the end of the paper, some educational considerations are offered. Kata kunci: Outcome-based education; learning outcomes; student assessment